A cross-sectional survey analysis of patient and family knowledge, confidence, and perceived barriers to reporting patient deterioration - Lisa Thiele; Arthas Flabouris; Campbell Thompson (PLoS ONE, 2025)
Background The knowledge, confidence, and skills of healthcare consumers to identify acute clinical deterioration and appropriately escalate concerns remain largely undetermined. This gap is despite the widespread international introduction of consumer escalation systems intended to provide patients and family an avenue to escalate their concerns if worried about deterioration in their own or relative’s condition during a hospital stay. Aim To explore patient and family knowledge of acute clinical deterioration, and their confidence and perceived barriers to escalating their concerns. Design Cross-sectional, in-person, consumer surveys across an Australian acute adult hospital. The study specific survey tool was developed through a multistage process with healthcare consumer input during creation and testing. Methods Questions explored healthcare consumer knowledge, confidence, and perceived barriers in association with acute clinical deterioration, recognising deterioration, and escalating concerns. Descriptive and inferential analysis was completed, and knowledge, confidence, and barrier scores established. Association between scores and consumer type, gender, age, education level, prior experience with clinical deterioration or rapid response team review, and hospitalisation history in the last 12 months were assessed using multivariable linear regression. Results 133 surveys were completed. Knowledge scores varied across respondents. Awareness of the local consumer escalation system was low. A positive association was identified between knowledge and confidence that diminished with increasing barrier scores. A strong negative correlation was present between barriers and confidence. No significant difference existed in knowledge, confidence, or barrier scores based on consumer type, gender, education level, previous experience with deterioration or rapid response team review, or hospitalisation history. Conclusions Limitations in patient and family knowledge may impede consumer escalation system success. Increasing knowledge may enhance patient and family confidence to identify deterioration and escalate concerns. However, barriers to consumer escalation decrease this potential. Interventions to increase consumer knowledge should therefore be accompanied by strategies to minimise barriers.